REESTRUTURAÇÃO URBANA E DAS CIDADES: MOSAICO E ABSTRAÇÃO ESPACIAL (REMUNOM, 2025)
Urban restructuring and city dynamics can be understood as broader and more complex concepts than the term "urban structure", which, according to urban geography scholars, refers to the spatial organization of the forms and functions of a city at a historical moment. specific. The definition of urban structure as the reality of the city conceived and represented on an abstract level. This understanding is reinforced by Sposito (1991), who describes the urban structure as a “mosaic”, the result of processes related to land use within the city and the continuous spatial reorganization, driven by the dynamics of economic activities. Furthermore, the residential function and the layout of leisure areas are considered important elements in this configuration. The objective of this article is to theoretically debate the understanding of urban restructuring and its multiple facets in the urban and the city. The methodology adopted was a bibliographic survey. In essence, an urban structure is not static, but reflects a series of continuous and interconnected transformations, which involves both the allocation and relocation of functions and spaces, meeting the demands of the population and the economy. Therefore, understanding the city requires the analysis of these sound processes that constantly shape the urban landscape.